Did the early Christians build churches?: revisiting the evidence - Turpin, Alexander (Joint liturgical studies, 2025)
This study proposes a new paradigm for understanding the evolution of Christian architecture prior to the Constantinian Peace (ca. 314 C.E.). Through close reading and textual criticism, the author revisits the written evidence for ante-pacem Christian architecture, contextualising it in the light of historical developments and the limited archaeological evidence. From this analysis, it is argued that early Christians did, in fact, possess a ‘churchgoing consciousness’. That is, the documents reveal that the earliest Christians gradually shifted away from a eucharistic praxis centered on the homes of the community patrons towards the communal use of dedicated worship centres, designed particularly for the liturgical needs of eucharistic worship. --